PENERAPAN METODE PEMBELAJARAN MIND MAPPING BERBANTUAN MEDIA WHATSAPP UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR IPA - I Wayan Darmayoga I Ketut Suparya (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2020)
This study aims to determine the use of mind mapping methods could increase the interest and learning achievements of science in fourth grade students of Elementary School number 1 Penatih in the academic year 2019/2020. This research consists of two cycles, each cycle consisting of four stages, namely planning, implementing actions, observing/evaluating, and reflecting. The subjects of this study were the fourth grade students of Elementary School number 1 Penatih, totally 24 people. The object of this study is the interest and learning achievements of Natural Sciences. The method of collecting the data are observation methods to collect data on student learning interest and test methods to collect the data on student learning achievements. Based on the results of the study can be explained that the average percentage of interest in learning science in pre-cycle reached 55.5%, the average percentage of science learning achievements reached 59% and classical completeness reached 20%. After the use of mind mapping methods in the first cycle the average percentage of students' learning interest increased to 65%, the average percentage of learning outcomes reached 65.9% and classical completeness reached 35%. With the improvement in cycle II the average percentage of interest in learning increased to 90%, the average percentage of student learning achievements increased to 75.5% and classical completeness reached 90%.